1999
DOI: 10.1086/315046
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Doxycycline Treatment on the Development of Protective Immunity in a Murine Model of Chlamydial Genital Infection

Abstract: Chlamydia trachomatis is a major cause of sexually transmitted disease (STD) worldwide. Antibiotics are effective in treating infection; however, reinfection is common. This observation has led to the conclusion that infection fails to elicit a protective antichlamydial immune response. It was postulated that high reinfection rates might be due to early eradication of organisms from genital tissue after antibiotic intervention, which could negatively influence the development of naturally acquired protective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 30 publications
6
68
0
Order By: Relevance
“…3 and 5), and some clusters remained for as long as 70 days postinfection (data not shown). In a recent study we demonstrated that the level of protective immunity that devel- ops following primary genital tract infection was significantly impaired if animals were treated with doxycycline before the infection resolved (39). The most significant effects were found when mice were treated prior to 10 days postinfection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…3 and 5), and some clusters remained for as long as 70 days postinfection (data not shown). In a recent study we demonstrated that the level of protective immunity that devel- ops following primary genital tract infection was significantly impaired if animals were treated with doxycycline before the infection resolved (39). The most significant effects were found when mice were treated prior to 10 days postinfection.…”
Section: Discussionmentioning
confidence: 96%
“…The in vitro production of cytokines by antigen-stimulated splenic lymphocytes has also been used to define the systemic cellular immune response following primary chlamydial genital tract infection (27,(37)(38)(39). In recent studies, the molecules that traffic lymphocytes to genital tract tissue following chlamydial infection have been defined using in situ immunohistochemical analysis (15,28).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting T cell populations were stained with the MHC tetramer as well as Abs against surface markers IL-7R (CD127) and CD62L (BD Pharmingen) and then sorted on a FACSCalibur flow cytometer (BD Biosciences). (17). Each mouse received 100 l of 3 mg/ml doxycycline hyclate (30 g per mouse at 10 mg/kg; Sigma-Aldrich).…”
Section: Phenotypic Characterization Of Memory Cell Populations Usingmentioning
confidence: 99%
“…To test whether the elimination of organisms that may be persisting below detectable levels would improve the ability of Chlamydia-specific memory cells to respond to antigenic challenge we treated mice with the antibiotic doxycycline before challenge. Treatment of mice with doxycycline within the first 3 days of infection has been shown to alter development of primary CD4 ϩ T cell responses by reducing the levels of available Ag (17). To ensure adequate priming of naive Chlamydia-specific CD8 ϩ T cells, we waited 7 days after we infected mice with C. trachomatis before initiating antibiotic treatment.…”
Section: Chlamydia-primed Cd8 ϩ T Cells Are Limited In Their Capacitymentioning
confidence: 99%
“…Furthermore, antibiotic therapy may increase the risk of infection with antibiotic-resistant bacteria (18) or disrupt beneficial effects of the microbiota on intestinal immune homeostasis (7,39). This has resulted in an ongoing controversy on whether antibiotic treatment might interfere with the generation of a protective immune response (54). However, systematic studies of these potentially adverse phenomena are scarce, and we do not know whether they are causally linked or which of them are causally linked.…”
mentioning
confidence: 99%